(untitled) (Journal of Hama University, 2020)
The research aims to identify the degree of the need of the students of the Faculty of Education at the University of Damascus for the skills of designing cognitive journeys through the Web in the second semester of 2018/2019. The sample of the study consisted of (320) male and female students from the third and fourth year students in the Faculty of Education at the University of Damascus /class teacher. The researcher used the Descriptive method to conduct the research. In order to reach the results of the research, the researcher designed the research tools represented by a questionnaire consisting of (6) main skills and each skill of a number of sub-skills. The study showed several results, the most important of which are: The degree to which the students of the College of Education needed the skills of designing cognitive journeys through the Web on the questionnaire as a whole was very large, with an average of (4.43) With regard to the sub-skills. The sixth skill (the skill of managing the Quest website) came first in terms of needs, and the first skill (skill to create a Web site Quest on google sites) came in the last place in terms of needs. The results were found there are no differences between the average scores of students on the questionnaire to identify the skills of designing cognitive journeys through the Web (Web Quest) according to the variable of the school year. The research reached a number of proposals, the most important of which are the following: Training courses for teachers on using the internet and utilizing them in the field of designing E-learning.